Characteristics of Natural Fiber Composites Materials Reinforced with Aluminum and Copper Powder for The Performance of Automatic Motorcycle Clutch Pad - Riyadi Riyadi; Ahmad Kholil; Januar Parlaungan Siregar; Siska Titik Dwiyati; Danang Budi Pratama; Ari Setiawan; Eko Arif Syaefudin (Universitas Muhammadiyah Magelang, 2023)
Currently, research on natural fiber composites (NFC) for automotive applications has attracted the attention of researchers and academics. Natural fibers such as coconut fiber and wood powder are mixed with metal materials such as aluminum and copper to obtain the composite characteristics of automatic motorcycle clutch pad materials. Coconut fiber and wood powder are suitable natural materials for composites and are easily obtained from waste. Natural fiber materials with metal reinforcement into composites are expected to produce materials suitable for friction materials such as clutch pads and brake pads with a good characteristic. This study aims to determine the characteristics of the coefficient of friction, wear, and hardness of NFC materials reinforced aluminum and copper powder for the performance of automatic motorcycle clutch pads. Experiments were carried out on various compositions of aluminum and copper powder. Tribometer testing was carried out to determine the friction coefficient and wear. Hardness testing using the Vickers method and testing the performance of automatic motorbikes with a chassis dyno test. The results show that the performances of the clutch pad with NFC-reinforced aluminum and copper show power and torque results that resemble the performances of genuine part materials in each operating cycle. The value of friction coefficient, wear, and hardness of this material are a value close to that of a genuine part clutch pad material. The improved performance of this material is expected to be considered in the manufacture of future clutch pads.